2014
DOI: 10.1371/journal.pone.0098956
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Expression Profiles of Reference Genes in Mouse Preimplantation Embryos of Different Ploidies at Various Developmental Stages

Abstract: Real-time reverse transcription quantitative polymerase chain reaction (qPCR) has become the most frequently used system for studies of gene expression. Manystudies have provided reliable evidence that the transcription levels of reference genes are not constant at different developmental stages and in different experimental conditions. However, suitable reference genes which are stably expressed in polyploid preimplantation embryos of different developmental stages have not yet been identified. Therefore, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…Several previous studies have provided evidence that transcription levels of reference genes from embryos did not express constantly in different developmental stages and under different production methods (Mamo et al 2007(Mamo et al , 2008Smits et al 2009;Gu et al 2014). In the present study, the differences in CT values of reference gene expression were observed in blastocysts produced by different in vivo and in vitro methods (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Several previous studies have provided evidence that transcription levels of reference genes from embryos did not express constantly in different developmental stages and under different production methods (Mamo et al 2007(Mamo et al , 2008Smits et al 2009;Gu et al 2014). In the present study, the differences in CT values of reference gene expression were observed in blastocysts produced by different in vivo and in vitro methods (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, an investigation focussed on the inefficiency of porcine SCNT embryos has revealed that abnormal patterns of developmental efficiency and gene expression were caused by incomplete reprogramming of the donor cell genome as well as aberrant epigenetic mechanisms related to DNA methylation and histone de-acetylation (Kumar et al 2007(Kumar et al , 2013Zhao et al Relative expressions of OCT4 2010). It has been reported that reference genes in early embryonic developmental stages were differentially expressed and hence the accurate assessment of gene expression could not be performed (Robert et al 2002;Mamo et al 2007Mamo et al , 2008Gu et al 2014). Gene expression of different embryos reflects their own characteristics, therefore, investigations should be focussed on increasing the accuracy of reliable reference genes for appropriate comparative gene expression studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations